2008
DOI: 10.3390/ijms9122333
|View full text |Cite
|
Sign up to set email alerts
|

Recognition Properties and Competitive Assays of a Dual Dopamine/Serotonin Selective Molecularly Imprinted Polymer

Abstract: A molecularly imprinted polymer (MIP) with dual dopamine/serotonin-like binding sites (DS-MIP) was synthesized for use as a receptor model of study the druginteraction of biological mixed receptors at a molecular level. The polymer material was produced using methacrylic acid (MAA) and acrylamide (ACM) as functional monomers, N,N′-methylene bisacrylamide (MBAA) as cross-linker, methanol/water mixture (4:1, v/v) as porogen and a mixture of dopamine (D) and serotonin (S) as templates. The prepared DS-MIP exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 39 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…Suedee et al examined the controlled delivery of chiral b-blockers and non-steroidal anti-inflammatory drugs through both oral and transdermal routes. [37][38][39][40][41][42][43][44] The release of S-propranolol (b-blocker) has been studied extensively in particular. Two different methods of polymerizing MAA with EGDMA as the crosslinker were explored: bulk polymerization and suspension polymerization.…”
Section: Introduction To Molecular Imprintingmentioning
confidence: 99%
“…Suedee et al examined the controlled delivery of chiral b-blockers and non-steroidal anti-inflammatory drugs through both oral and transdermal routes. [37][38][39][40][41][42][43][44] The release of S-propranolol (b-blocker) has been studied extensively in particular. Two different methods of polymerizing MAA with EGDMA as the crosslinker were explored: bulk polymerization and suspension polymerization.…”
Section: Introduction To Molecular Imprintingmentioning
confidence: 99%
“…MIP sensors could be considered as best alternatives to biosensors, primarily in terms of higher shelf lives and biomimetic characteristics. With the recent advent of multi/double-imprinting in a single polymer format, multicomponents often present in a sample can simultaneously be analyzed in the cost-effective manner saving both time and labor [21][22][23][24][25][26][27][28][29][30][31]. However, such analysis was rather challenging in many cases owing to the overlapped analyte signals and matrix effect.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a molecularly imprinted polymer with dual dopamine=serotonin-like binding sites was developed to study interactions between drugs and biological mixed receptors. [30] Similarly, a non-covalent MIP of serotonin was used to platelet rich plasma. [31] Recent studies have shown the use of monolithic molecularly imprinted polymer as a chiral support for the separation of neurotransmitters by capillary electrochromatography.…”
Section: Introductionmentioning
confidence: 99%